2015
DOI: 10.17227/01203916.68rce19.40
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Image of Teachers: A Ten-Country Perspective

Abstract: Docente, imagen del maestro, profesión docente, Letonia. ResumenDebido a la interacción social en el proceso de enseñanza-aprendizaje se ha formado una imagen del maestro en la mente de los estudiantes, que posteriormente se reproduce en el espacio público. Entendemos imagen como el fenómeno que se desarrolla en la conciencia humana como resultado de la experiencia social en forma de sistemas de signos. La investigación muestra que la imagen del maestro en el espacio público no siempre es positiva. En consecue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The teachers' and children's hairstyles were ordinary and similar. Kestere and Kalke's (2015) research revealed that respondents emphasized more informal than formal dressing of the teacher. Comparing the groups, a couple of female teachers in the 1992 and 2008 drawings wore dresses and aprons or skirts and shirts, but none of the teachers wore these clothes in the 2013 and 2017 drawings.…”
Section: Images Of the Teacher And The Childrenmentioning
confidence: 98%
See 3 more Smart Citations
“…The teachers' and children's hairstyles were ordinary and similar. Kestere and Kalke's (2015) research revealed that respondents emphasized more informal than formal dressing of the teacher. Comparing the groups, a couple of female teachers in the 1992 and 2008 drawings wore dresses and aprons or skirts and shirts, but none of the teachers wore these clothes in the 2013 and 2017 drawings.…”
Section: Images Of the Teacher And The Childrenmentioning
confidence: 98%
“…Images and their meanings are created in perceptions and based on the person's former experiences and interactions with their environment (Kestere and Kalke 2015;Nóvoa 2000). Images involve memory fragments, symbols and interpretations of feelings, ideas and phenomena (Emmison and Smith 2000).…”
Section: Theoretical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Latvian historians of education also enthusiastically picked up «visual turn» in the history of education (see: Ķestere & Kaļķe, 2015;Kestere, Wolhuter & Lozano, 2012). Usage of visual sources made narratives of history of education more orientated towards school reality (e.g., photos taken in classrooms), more personal and consequently raised interest of students about the history of education.…”
Section: Lb: According To Your Experience In Latvia and In Europe mentioning
confidence: 99%